Targeted Transplantation of Human Umbilical Cord Blood Endothelial Progenitor Cells with Immunomagnetic Nanoparticles to Repair Corneal Endothelium Defect - Shao, Chunyi (Stem Cells Dev, 2015)
Corneal endothelial dysfunction involves progressive corneal edema and loss of visual acuity, which result in the need for corneal transplantation. The global shortage of donor corneas limits the development of the surgery. Reconstruction of a bioengineered corneal endothelium might resolve this problem. Various scaffolds have been used, but poor biocompatibility and degradation limit their applications. In this study, a novel method of targeted cellular transplantation without permanent residence of cell carriers in the host was proposed. Human umbilical cord blood endothelial progenitor cells (UCB EPCs) were labeled with CD34 immunomagnetic nanoparticles. The efficiency of the magnet attraction was evaluated in vitro with a simple device simulating the anterior chamber. The UCB EPCs labeled with nanoparticles were transplanted into the anterior chamber of rabbits with magnet attraction. The results indicated that labeling the nanoparticles did not affect the proliferation of the UCB EPCs. The in vitro study indicated that the magnet could directionally attract UCB EPCs labeled with nanoparticles. The in vivo study indicated that the corneas in rabbits transplanted with UCB EPCs labeled with nanoparticles and magnet attraction became relatively transparent with little edema. These results showed that UCB EPCs labeled with CD34 immunomagnetic nanoparticles could be attracted directionally by a magnet and could repair corneal endothelial defects, providing a promising cell therapy for corneal endothelial dysfunction.